INTERNAL PR AS PART OF CORPORATE CULTURE - O. Goryacheva (Вестник университета)
The identification of mechanisms for the implementation of public relations and the selection of effective internal PR tools can affect the organization’s management. The main objective of internal PR is to stabilize the workforce and increase employee satisfaction. The possibilities of internal PR in the formation and maintenance of corporate culture have been investigated in the article. The indicators of labor assessment presented not only help determine the level of professionalism of the employee, but also demonstrate his personalized labor achievements to the whole team. The motivation of the participants of the labor process to the awareness of the importance of the implementation of the collective tasks has a beneficial effect on the formation of corporate culture. Monitoring of events and internal PR tools will allow you to adjust the formation of corporate culture and provide a high level of management at the enterprise.